Rising through Cities in Ghana : Ghana Urbanization Review Overview Report - World Bank Group (World Bank, Washington, DC, 2015)
Rapid urbanization in Ghana over the past three decades has coincided with rapid GDP growth. This has helped to create jobs, increase human capital, decrease poverty, and expand opportunities and improve living conditions for millions of Ghanaians. Ghana’s urban transformation has been momentous, but it is not unique: a similar process has characterized other countries at similar levels of development. Ghana’s key challenge now is to ensure that urbanization continues to complement growth through improvements in productivity and inclusion, rather than detracting from these goals. Many rising problems are related to efficiency and inclusion: these include slums, lack of basic services, underdeveloped manufacturing, and insufficient transport infrastructure.